2011
DOI: 10.1002/path.2847
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the molecular pathogenesis of chordoma: a new paradigm for molecular targeting of rare cancers

Abstract: Abstract‘Chordoma’ represents orphan sarcoma subtypes in which systemic treatments have so far proved ineffective. Two original papers in the Journal of Pathology have recently elucidated important steps of its molecular oncogenesis. The demonstration of gains of copy number of both T (brachyury homologue) and EGFR (epidermal growth factor receptor) genes in chordoma, as well as of their role in promoting cell proliferation, offers a strong preclinical rationale for exploring the inhibition of their products a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It may also account for the limited value of single targeted therapies in patients with chordoma, for example antagonists to EGFR, and ckit/PDGFR , , . Given this background, and that chordoma has a poor prognosis with limited therapeutic options , we consider that targeting brachyury directly using RNA interference‐mediated gene therapy, or other methodologies , has a biologically justifiable rationale.…”
Section: Discussionmentioning
confidence: 99%
“…It may also account for the limited value of single targeted therapies in patients with chordoma, for example antagonists to EGFR, and ckit/PDGFR , , . Given this background, and that chordoma has a poor prognosis with limited therapeutic options , we consider that targeting brachyury directly using RNA interference‐mediated gene therapy, or other methodologies , has a biologically justifiable rationale.…”
Section: Discussionmentioning
confidence: 99%
“…Presneau et al (50) and Dei Tos (53) demonstrated that close to half of the investigated chordoma cases showed a gain of chromosome band 6q27 (the locus wherein BRACHYURY locates) either through polysomy of the entire chromosome 6 or structural rearrangements, which indicates that cCNGs of BRACHYURY are pathogenetically relevant in sporadic chordoma. Cho et al (35) and Pillay et al (54) demonstrated that a common single-nucleotide polymorphism (SNP) located in the BRACHYURY gene, rs2305089, has strong association with the risk of sporadic chordoma.…”
Section: The Genetic Basis Of Brachyury Expression In Chordomamentioning
confidence: 98%
“…Chordoma accounts for approximately 1-4% of all bone tumors (3) and has a population-based incidence rate of 0.8/1000000 (4). The peak age for chordoma onset ranges from 60 to 70 years (5)(6)(7)(8). Chordomas most commonly involve the sacrococcygeal or skull base (9), and cases occurring outside the axial skeleton have also been reported (10).…”
Section: Introductionmentioning
confidence: 99%